Mentoring Model of Business Plan Competition Program in Improving Social Entrepreneuship - Saripah, Iip; Lestari, Retno Dwi; Putra, Ari; Mutamam, Muhammad Hadi Ali (Journal of Nonformal Education, 2022)
The integration of entrepreneurship education is one of competences under the lifelong education concept. Entrepreneurship gives a relevant perspective in deciding the best way for students as preparation to face the future. This study was conducted to enhance the students’ entrepreneurship through business plan competition. The method applied was qualitative method with field research approach that the information was from the research objects which were the participants. The research subjects were students of Community Education Department UPI who participated in the competition. The result showed that mentoring is a kind of accompaniment to support and encourage students in developing their business. Business developed in social entrepreneurship, both commercial and non-commercial, is related to scientific development of community education. Mentoring can encourage the aspiring entrepreneurs to facilitate marketing and to implement their developed business plan.